2021
DOI: 10.1039/d1dt00971k
|View full text |Cite
|
Sign up to set email alerts
|

Single-composition Al3+-singly doped ZnO phosphors for UV-pumped warm white light-emitting diode applications

Abstract: The development of full-visible-spectrum phosphors is essential for next-generation light-emitting devices with better light quality. Herein, we report on a novel broad-band-emitting phosphor based on single-composition Al-doped ZnO phosphor. Under...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 102 publications
1
20
0
Order By: Relevance
“…35 It was reported that the lattice constants (a,c), the unit cell volume (V), the bond length (L) of Zn-O atoms, the strain along the c-axis, and the crystalline size of undoped ZnO and ZnO:Cu 2+ powder could be derived from the XRD patterns. 19,28,[36][37][38] The calculated structural parameters are listed in Table 1, showing excellent consistency with previous reports. 37 The larger "c" value of ZnO:5%Cu 2+ phosphors annealed at various temperatures compared with that of the undoped ZnO could be explained by the diffusion of Cu 2+ ions into the ZnO host lattice, generating oxygen vacancies.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…35 It was reported that the lattice constants (a,c), the unit cell volume (V), the bond length (L) of Zn-O atoms, the strain along the c-axis, and the crystalline size of undoped ZnO and ZnO:Cu 2+ powder could be derived from the XRD patterns. 19,28,[36][37][38] The calculated structural parameters are listed in Table 1, showing excellent consistency with previous reports. 37 The larger "c" value of ZnO:5%Cu 2+ phosphors annealed at various temperatures compared with that of the undoped ZnO could be explained by the diffusion of Cu 2+ ions into the ZnO host lattice, generating oxygen vacancies.…”
Section: Resultssupporting
confidence: 86%
“…002), ( 101), ( 102), ( 110), ( 103), ( 200), (112), and (201) planes of the hexagonally structured ZnO phase (F63mc space group, JCPDS 36-1451). 19,28 At the higher annealing temperature of 1200 °C, a new diffraction peak emerged at 2θ of 38.8°, corresponding to the (111) plane of the CuO phase (JCPDS 05-0661). 22,33,34 As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a sharp emission peak at 395 nm from the NUV chip and red emissions in the 580–710 nm wavelength region is obvious in the EL spectrum of the GdYGd:Eu 3+ -coated LED prototype. The quantum efficiency (QE) of GdYGd:20 mol% Eu 3+ phosphor can be estimated using the following eqn (1): 59,60 where L S is the emission spectrum from the phosphor, and E R and E S correspond to the excitation spectra without and with the phosphor, respectively. 8,61…”
Section: Resultsmentioning
confidence: 99%
“…The chromaticity coordinates of the n-ZnO NRs/p-BDD heterojunction shift in the white light region with aluminum doping, from (0.2943, 0.3052) to (0.2957, 0.2907), where the emission intensity of the n-Al:ZnO NRs/p-BDD heterojunction is enhanced and the chromaticity coordinates (0.2957, 0.2907) are closer to the standard white light, as shown in the figure. The outstanding broadband WLED emission of the n-Al:ZnO NRs/p-BDD heterojunction makes it an interesting candidate material for WLED devices [ 45 ].…”
Section: Resultsmentioning
confidence: 99%